An alternative dosing strategy for ropeginterferon alfa-2b may help improve outcomes in myeloproliferative neoplasms: An overview of previous and ongoing studies with perspectives on the future - Qin, Albert; Urbanski, Raymond W.; Yu, Lennex; Ahmed, Tasfia; Mascarenhas, John (Frontiers in Oncology, 2023)
Ropeginterferon alfa-2b is a novel, long-acting mono-pegylated proline-IFN-alpha-2b approved for treatment of polycythemia vera in adults, regardless of thrombotic risk level or treatment history. Clinical trial data indicate the dose and titration of ropeginterferon alfa-2b is safe and effective. However, additional studies may provide rationale for an amended, higher initial dosage and rapid titration. This article is an overview of current and upcoming studies of ropeginterferon alfa-2b in myeloproliferative neoplasms that support the exploration of an amended dosing scheme in order to optimize patient tolerability and efficacy outcomes.